Radiological Effects of Changes in Entry Points on the Medial Longitudinal Arch during Longitudinal Arch Lateral Projections - Hong, Dong-Hee; Joo, Young-Cheol (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The flatfoot and claw-foot are diagnosed mainly by measuring the degree of cu rvature of the arch of the foot. However, if the incidence point varies, the medial arch curvature in the im age may change. This change can increase the error rate and frequency of retakes, thereby increasing the dose of radiation to the patient. The purpose of this study was to investigate the importance of using the c orrect point of incidence and effect of the point of incidence on the radiologic finding of the medial arch. Methods/Statistical analysis: The GC-85A radiation generator and phantom foot and ankle were used, and heights of the incidence point were set to the plantar base, metatarsal bone, ankle bone, and ankle jo int. The phantom was located on the front side, and the central X-ray was incident in the outward and in ward directions. Five radiology students obtained a total of 40 images, ten times at each incidence point after pre-training. The statistical program SPSS was used to calculate the average and analyze the sum. I n order to express the width of the mean increase and decrease based on the change in the incidence poi nt, it was calculated by setting the reference point as the foot bone. Findings:When the incidence point was changed to the plantar base, the angle between the tibia and th e first metatarsal bone changed by 3.4%; the angle between the tibia and the calcaneus pitch changed by 0.55%; the angle between the calcaneus and the first metatarsal bone changed by 0.62%; the height of th e calcaneus changed by 0.5%, the height of the longitudinal joint changed by 3.04%; the cubic bone heig ht decreased by 5.63%; the tongue bone height decreased by 2.97%; and the first medial bone height cha nged by 6.19%. Improvements/Applications: Upon changing CR to the ankle joint, the talo–first metatarsal angle decre ased by 12.96%, but the calcaneal pitch angle, calcaneo–first metatarsal angle, calcaneal height, calcaneo cuboid joint height, cuboid height, cuneiform height, and first metatarsal height increased by 5.9%, 9.56%, 5.05%, 4.39%, 5.93%, 6.73%, and 16.81%, respectively. This study suggests that the effect of changes in the incidence point on the curvature of the medial arch is important.